2021
DOI: 10.1111/trf.16722
|View full text |Cite
|
Sign up to set email alerts
|

Development of a preoperative risk score predicting allogeneic red blood cell transfusion in children undergoing spinal fusion

Abstract: Background Children undergoing spinal fusion often receive blood products. The goal of this study was to develop a preoperative score to help physicians identify those who are at risk of allogeneic red blood cell (RBC) transfusion. Study design and methods This retrospective study of children undergoing spinal fusion in the ACS‐NSQIP Pediatric database (2016–2019) aimed at identifying risk factors associated with allogeneic RBC transfusion. Univariable logistic regression and multivariable logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Based on our prior work 44 demonstrating that anemia is an independent predictor of ARBT rate, and the observed association between ARBT and infections, we expected to find a stronger relationship between anemia and infection in our unadjusted analysis. However, we previously showed the impact of anemia on ARBT to be less pronounced in younger patients and in those with neuromuscular scoliosis 44 , groups found in the present study to be at the greatest risk of postoperative infection. Studying a heterogeneous group with disparate risks of infection dictated in large part by deformity type may have thus minimized any impact of preoperative anemia.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Based on our prior work 44 demonstrating that anemia is an independent predictor of ARBT rate, and the observed association between ARBT and infections, we expected to find a stronger relationship between anemia and infection in our unadjusted analysis. However, we previously showed the impact of anemia on ARBT to be less pronounced in younger patients and in those with neuromuscular scoliosis 44 , groups found in the present study to be at the greatest risk of postoperative infection. Studying a heterogeneous group with disparate risks of infection dictated in large part by deformity type may have thus minimized any impact of preoperative anemia.…”
Section: Discussionmentioning
confidence: 95%
“…These findings strengthen evidence for an association between ARBT and postoperative infections in children treated with spinal fusion. To the extent that the need for ARBT may be reduced through risk stratification and targeted preventive measures, including the treatment of preoperative anemia and other blood conservation strategies, we hope that further study can contribute to a reduction in postoperative infections and associated morbidity 40 , 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the DD patients, the mean (SD) length of stay was increased (4.1 [3.5] days without transfusion vs. 4.6 [6.7] days with transfusion; p = 0.49), likely owing to a more extensive surgical procedure. Similarly, multiple studies have identified a decrease in the rate of allogeneic packed red blood cells (PRBC) transfusion in children over time, likely owing to more conservative thresholds in transfusion guidelines [14–17].…”
Section: Discussionmentioning
confidence: 99%